2002
DOI: 10.1002/ijc.10230
|View full text |Cite
|
Sign up to set email alerts
|

ZD1839 (IRESSA), an EGFR‐selective tyrosine kinase inhibitor, enhances taxane activity in bcl‐2 overexpressing, multidrug‐resistant MCF‐7 ADR human breast cancer cells

Abstract: Constitutive bcl-2 overexpression increases the tumorigenic and metastatic potential of doxorubicin-resistant, estrogen-independent, MCF-7 ADR human breast cancer cells. We evaluated the sensitivity to taxanes (paclitaxel, docetaxel and IDN 5109) of 2 bcl-2-overexpressing MCF-7 ADR clones and control neomycin-transfected MCF-7 ADR neo cells. The 2 bcl-2-overexpressing MCF-7 ADR clones were relatively resistant to all 3 taxanes, whereas the MCF-7 ADR neo cells were relatively resistant to paclitaxel and docetax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 12 publications
0
57
0
Order By: Relevance
“…Blockade of the EGFR signalling pathways results in not only retardation of cell cycle progression but also induction of apoptosis in EGFR-expressing tumour cells. It has been suggested that the cell cycle retardation is mediated by an increase in the expression level of a CDKI p27 (Moasser et al, 2001;Albanell et al, 2002;Janne et al, 2002), and that the induction of apoptosis is mediated by a decrease in the expression level of an antiapoptotic protein Bcl-2 Ciardiello et al, 2002;Nicholson et al, 2002) or by activation of a proapoptotic protein BAD (Gilmore et al, 2002). Very recently, it has been reported that the EGFR-TKI gefitinib increases both p27 and p21 proteins associated with CDK2 -cyclin-E and CDK2 -cyclin-A complexes in HER1-overexpressing head and neck squamous carcinoma cells (Di Gennaro et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blockade of the EGFR signalling pathways results in not only retardation of cell cycle progression but also induction of apoptosis in EGFR-expressing tumour cells. It has been suggested that the cell cycle retardation is mediated by an increase in the expression level of a CDKI p27 (Moasser et al, 2001;Albanell et al, 2002;Janne et al, 2002), and that the induction of apoptosis is mediated by a decrease in the expression level of an antiapoptotic protein Bcl-2 Ciardiello et al, 2002;Nicholson et al, 2002) or by activation of a proapoptotic protein BAD (Gilmore et al, 2002). Very recently, it has been reported that the EGFR-TKI gefitinib increases both p27 and p21 proteins associated with CDK2 -cyclin-E and CDK2 -cyclin-A complexes in HER1-overexpressing head and neck squamous carcinoma cells (Di Gennaro et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Actin or a-tubulin was used as the internal control. radiation or cytotoxic agents, such as taxanes and cisplatin, synergistically inhibit the growth of tumour cells both in vitro and in vivo (Ciardiello et al, 2000;Sirotnak et al, 2000;Ciardiello et al, 2001;Bianco et al, 2002;Ciardiello et al, 2002;Huang et al, 2002;Magne et al, 2002;Williams et al, 2002). However, no synergistic or additive activity has been reported with gefitinib and a cytotoxic agent in phase III clinical trials Johnson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various mechanisms underlying taxane resistance that have been previously described [27]. In several in vitro studies, it was demonstrated that excessive Bcl-2 expression or impaired phosphorylation was responsible for taxane (docetaxel and paclitaxel) resistance; however, an opposite finding was reported by Ferlini et al, who suggested that Bcl-2 down regulation was responsible for paclitaxel resistance [28,29,30]. Additional conflicting results from several clinical studies have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule tyrosine kinase inhibitors (e.g., anilinoquinazoline compounds such as gefitinib and erlotinib), which are ATP analogues, 2,3,34,46,51 have been shown to exhibit growth inhibitory effects against a wide variety of human tumors. [13][14][15][16][17] The RTK inhibition approach has shown promise in some clinical trials, but results have been quite mixed. 19 In particular, despite the promise in a small (demographic) subpopulation with significantly advanced disease, clinical responses to gefitinib and erlotinib varied among population samples.…”
Section: Introductionmentioning
confidence: 99%